Deciphering hemipelagites from homogenites through anisotropy of magnetic susceptibility. Paleoseismic implications (Sea of Marmara and Gulf of Corinth) - Campos, Corina; Beck, Christian; Crouzet, Christian; Demory, Francois; Van Welden, Aurelien; Eris, Kadir (Elsevier, 2013)
In closed marine basins and large lakes, gravity re-depositional processes often result in specific turbidites with two abruptly separated layers: a coarse graded lower term and an upper homogenous fine-grained term. An additional mixed term generally occurs in between, indicating to and from particle displacements. The later ones are related to oscillating bottom currents responsible for a high increase of the fine fraction segregation, within the reworked wasted mass. The whole sedimentary event is the association homogenite + turbidite (HmTu), which specific a settling condition area here characterized through Anisotropy of Magnetic Susceptibility (AMS). Homogenites's magnetic foliation appears anomalously high with respect to their expected state of compaction, and strikingly higher than hemipelagites's values. We applied this approach to Late Pleistocene/Holocene sediments from the Sea of Marmara and from the Gulf of Corinth. Grain-size and other magnetic parameters related to mineralogy are added to better assess the granular array influence on AMS. As HmTu is considered as often related to earthquake-triggering and tsunami/seiche effects, AMS appears as a useful tool for subaqueous paleoseismic investigations. First, it may evidence the signature of paleo-earthquakes; second, it permits to decipher hemipelagic intervals which are inferred to represent the time elapsed between two successive reworking events. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Homogenite; Turbidite; Magnetic fabric; Paleoseismicity; Marmara; Corinth